2021
DOI: 10.2147/pgpm.s320128
|View full text |Cite
|
Sign up to set email alerts
|

A Chinese Boy with Mowat–Wilson Syndrome Caused by a 10 bp Deletion in the ZEB2 Gene

Abstract: Purpose Mowat–Wilson syndrome (MWS) is a rare complex malformation syndrome which is characterized by typical facial dysmorphism, moderate to severe intellectual disability, global developmental delay, and multiple congenital anomalies. Here, we summarize the clinical characteristics and gene mutation analysis of a Chinese boy with MWS. Patients and Methods The clinical features of the patient were monitored. DNA extracted from peripheral blood was subjected to sequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…To date, more than 300 individuals with MWS have been reported in different regions of the world. And nearly 280 variants in ZEB2 have been identified (HGMD database; Wei et al, 2021 ; Zhang et al, 2021 ; Hu et al, 2020 ; Ma et al, 2020 ; Zou et al, 2020 ) ( Supplementary Table S1 ). However, Chinese MWS individuals have been infrequently reported ( Supplementary Table S2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, more than 300 individuals with MWS have been reported in different regions of the world. And nearly 280 variants in ZEB2 have been identified (HGMD database; Wei et al, 2021 ; Zhang et al, 2021 ; Hu et al, 2020 ; Ma et al, 2020 ; Zou et al, 2020 ) ( Supplementary Table S1 ). However, Chinese MWS individuals have been infrequently reported ( Supplementary Table S2 ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, more than 300 individuals with MWS have been reported in the literature, and approximately 280 variants in ZEB2 have been identified (HGMD database; Wei et al, 2021 ; Zhang et al, 2021 ; Hu et al, 2020 ; Ma et al, 2020 ; Zou et al, 2020 ). However, Chinese MWS individuals are relatively less described, and only 27 MWS cases and 23 pathogenic ZEB2 variants have been reported for Chinese individuals ( Balasubramaniam et al, 2010 ; Jiang et al, 2016 ; Hu et al, 2018 ; Wang et al, 2019 ; Ho et al, 2020 ; Hu et al, 2020 ; Ma et al, 2020 ; Wu et al, 2020 ; Zou et al, 2020 ; Wei et al, 2021 ; Zhang et al, 2021 ). Furthermore, phenotypic differences between Chinese and Caucasian MWS individuals have been less delineated.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the diversity of clinical phenotypes, MWS is di cult to be diagnosed clinically. Currently, more than 300 MWS patients have been reported [11][12][13] , and more than 280 ZEB2 variants have been found. However, only 35 cases of MWS and 25 pathogenic ZEB2 variants were reported in China [11,[15][16][17][18] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the incidence of the disease is about 1:50, 000 to 1:70, 000 [10] . By reviewing the literature, it can be found that about 300 MWS patients have been reported, and about 280 ZEB2 variants have been found (Human Gene Mutation Database) [11][12][13][14] . 35 cases of MWS and 25 pathogenic ZEB2 variants have been reported in China [11,[15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…Protein domain regions coded by exons are represented based on codon location within the domains (e.g., exon 9 codes for C-ZFa and exon 10 codes for C-ZFb). References are listed in brackets [ 6 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Figurementioning
confidence: 99%